Investigating dynamics of beating vibration system with one degree of freedom on elastic foundation - Tran Van Tuan; Do Sanh; Phan Van Thao (Vietnam Journal of Mechanics)
In this paper an analytical method for studying dynamics of a beating-vibration system on elastic foundation with the aid of computer is presented. The obtained results will be applied to the calculation and optimal design of vibration machines worked by the above represented principle.